Study of the effect of freezing on the visco-elastic properties of strawberries - Fundo, J. (2011)
The objective of this work was to study the influence of freezing on the visco-elastic properties of strawberries. Food structure plays an important role in food quality and functionality. It is important for the consumers to find an identical sensation when they eat a fresh strawberry and when the strawberry is defrosted. The visco-elastic properties of a food product are an indirect measure of its structure. Experimental measurements of these properties may correlate to changes on the physical attributes of the product. In this work, a dynamic mechanical analyser was used to assess changes on loss (E’’) and storage (E’) modulus, applying a compressive test with a Ø1.5 cm parallel plate geometry. Strawberries were acquired in a local market and frozen in a blast and fluidized bed freezer at –30 ºC for 1 hour. Samples were stored at –30 ºC in freezing chambers. Analyses were performed on fresh strawberries, after freezing and during storage. The samples were cut in small cylinders (1.5cm x 1.5cm) and left to relax during 1 hour at room temperature. Preliminary tests were performed in order to evaluate the linear visco-elastic region and the loss and storage modulus were determined. A dynamic frequency sweep test was also performed. Results showed that the behaviour of fresh strawberry sample varies significantly when compared with a defrosted sample. The influence of the storage still cannot be evaluated and is currently under study. Overall, it can be concluded that the freezing process greatly influenced the visco-elastic properties of the strawberries.